Visual social-emotional attention in ADHD including the impact of autism - Kochhar, Puja (2020)
ADHD is a common neurodevelopmental condition with poor long-term outcomes. The core problem that this project sought to address is a common clinical issue encountered in children with ADHD presenting to services with impairing social cognitive difficulties, including poor emotion recognition. The aim was to understand if emotion recognition difficulties were a primary consequence of abnormal patterns of visual attention in ADHD or alternatively social processing difficulties typically found in autism. Findings from two novel independent study samples demonstrated that visual attention to faces in children with ADHD (ADHD and ASD+ADHD) differed from children without ADHD (ASD and typically developing controls) using a 2x2 factorial approach. Specifically, children with ADHD (ADHD and ASD+ADHD) showed an atypical ‘hyper-extensive’ scanning of emotional faces compared to those without ADHD (ASD and typically developing controls). In contrast, Children with ASD (ASD and ASD+ADHD) were slower to orient to faces in ADOS (Autism Diagnostic Observation Schedule) pictures compared to those without ASD (ADHD and typically developing controls). Findings were in keeping with different visual attention profiles in ADHD compared to ASD with overlapping features in the comorbid group, indicating true comorbidity. Differentiation of visual social-emotional attention was also found at the group level using machine learning and discriminant function analysis, and the highest classification rate of 88% was found for the ADHD group. The findings of this research have implications for the diagnosis and the management of ADHD and associated social-emotional impairments.